Synthesis and Crystal Structure of a Cu(II) Complex with a Thiazole Containing Derivative of 1,5-Diazacyclooctane - Xu, Qiang; Zha, Ru-Hua; Meng, Jiang-Ping; Wang, Zhao-Dong; Chen, Feng-Ming (Asian Journal of Chemistry, 2013)
A new binuclear Cu(II) complex [Cu2(L)2·(H2O)·(ClO4)](ClO4)3 (L=1,5-bis-(5H-1l4-thiazol-4-ylmethyl)-1,5-diazocane) was synthesized and characterized by elemental analysis, IR spectroscopy and X-ray analysis. The complex crystallizes in orthorhombic system, space group P2(1)2(1)2(1) with a = 14.931(5), b = 16.041(6), c = 18.700(7), V = 4479(3)Å3, Dc = 1.720 g/Cm3, Z = 4, F(000) = 2368, μ(MoKa) = 0.71073 mm-1, R = 0.0738 and wR = 0.1460 for 7885 observed reflections (I > 2s(I)). X-ray analysis reveals that both copper(II) metal ion display a square pyramidal geometry with different coordination modes. Each copper is five-coordinated by four N from the ligand and one O form water molecule in Cu(1) and one O atom from perchlorate anion in Cu(2), respectively.